INTERPRETATION CHALLENGES OF ENGLISH ANALYTICAL TERMS FOR EFL LEARNERS: A LINGUISTIC STUDY OF SEMANTIC TRANSPARENCY AND CONTEXTUAL CUES - Zhuzhuna Gumbaridze; Tamta Popkhadze (International Journal of Innovative Technologies in Social Science, 2025)
This study explores the interpretation challenges posed by English analytical terms among B2-level EFL learners, emphasizing the multidimensional factors that influence semantic comprehension. Analytical terms—lexical units encoding complex, domain-specific concepts—are ubiquitous in academic and professional discourse but often lack semantic transparency, creating significant cognitive and linguistic barriers for non-native speakers. Employing a mixed-methods design, the research investigates learner engagement with selected terms from the EMN (European Migration Network) Asylum and Migration Glossary across three stages: a structured questionnaire, a multiple-choice test on isolated terms, and a contextualized comprehension task. The analysis examines how linguistic phenomena such as polysemy, synonymy, and homonymy contribute to semantic ambiguity and misinterpretation, and evaluates the role of contextual metadata—definitions, examples, and usage cues—in facilitating accurate comprehension. Findings indicate that learners struggle to interpret analytical terms when presented in isolation, particularly when lexical components do not transparently reflect the underlying institutional or conceptual meaning. Terms such as talent partnership and single permit exemplify how semantic opacity and cross-contextual variation hinder intuitive understanding. However, comprehension improves markedly when terms are embedded in authentic discourse, underscoring the importance of contextual framing. The study also identifies learner strategies for decoding and retaining specialized vocabulary, including contextual inference, morphological analysis, and reliance on prior domain exposure. By integrating linguistic, cognitive, and contextual dimensions, this research contributes to both terminology studies and EFL pedagogy. It highlights the pedagogical imperative to incorporate term-focused instruction into curriculum design and to develop targeted resources that enhance learners’ accuracy, fluency, and confidence in navigating academic and professional texts.